Predictive Factors of Amputation for Post-Bypass Surgery on Vascular Trauma Patients - Kusworo, Afila Reza; Soebroto, Heroe; Suroto, Heri (Faculty of Medicine, Universitas Padjadjaran, 2024)
n Indonesia, most vascular trauma is linked to traffic collisions. According to the Statistics Indonesia (Badan Pusat Statistik, BPS), there were 116,411 accidents in 2019. Limb salvages become important in vascular trauma, which is performed through, among others, vascular bypass surgery. However, secondary amputation still occurs after vascular bypass. This study aimed to determine the predictors of secondary amputation after vascular bypass due to vascular trauma. This study used descriptive analysis of medical records and univariate analysis. Medical records of patients with vascular trauma underwent vascular bypass in Dr Soetomo Regional Hospital, Indonesia, from January 2018 to December 2020 were collected. Independent variables were age, MESS, time interval between the incident of trauma to the first incision of bypass surgery, penetrating and blunt injury, injured arterial segment, multiple injuries, and obesity. The dependent variable was secondary amputation. Fisher Exact Test was used to analyze the correlation between dependent and independent variables. Results showed a significant difference between patients with a MESS score of >7 and those with a MESS score of ≤7 (p=0.044), where more patients with a MESS score of >7 experienced secondary amputation. Other variables showed no significant difference (p>0.05). This study concluded that MESS could be used as a predictor of secondary amputation in vascular trauma after vascular bypass. Further studies using multivariate analysis and a larger sample need to be conducted to get further insights on this phenomenon.